Social Capital and Lifestyle Impacts on Mental Health in University Students in Colombia: An Observational Study - Sotaquirá, Lina; Backhaus, Insa; Sotaquirá, Paula; Pinilla-Roncancio, Mónica; González-Uribe, Catalina; Bernal, Raquel; Galeano, Juan José; Mejia, Natalia; La Torre, Giuseppe; Trujillo-Maza, Elena M.; Suárez, Daniel E.; Duperly, John; et al. (Frontiers in Public Health, 2022)
Introduction For young adults, the first year of higher education represents a transition period into adulthood associated with an increased risk of developing depression, anxiety, and stress, contributing to deteriorating physical and mental health. The present study aimed to analyze the relationship between depressive symptoms and social capital and lifestyles among Colombian university students. Methods In 2020, a longitudinal repeated measures study was conducted on first year students at Universidad de los Andes in Bogota, Colombia. The study was conceptualized and approved by the university before the COVID-19 pandemic appeared. Each student completed a self-administered questionnaire including questions on sociodemographic characteristics, depressive symptoms, perceived stress, social capital, and lifestyles. The study's pilot was conducted in November 2019, and the two measurement points were in January 2020 (wave 1, before the COVID-19 pandemic was declared) and in August 2020 (wave 2, during the COVID-19 pandemic). A binary logistic regression analysis was performed to assess the relationship between depressive symptoms, perceived stress, social capital, and lifestyles. Findings A total of 609 first year students (response rate = 58.11%) participated in wave 1, and 42% of the participants showed signs of clinically relevant depressive symptoms. In wave 2, despite the difficulties encountered in collecting data due to the COVID-19 pandemic, 216 students from wave 1 participated (35.47%). An increase in a sedentary lifestyle was observed (31.49%). We found that cognitive and behavioral social capital levels decreased by 12.03 and 24.54%, respectively. In addition, we observed a 6.5% increase in students with clinically relevant depressive symptoms compared to wave 1. A low level of behavioral [OR: 1.88; 95% CI (1.16, 3.04)] social capital was associated with clinically relevant depressive symptoms. Conclusion The health of university students continues to be a public health concern. The study suggests that social capital may play an important role in preventing depressive symptoms. Therefore, universities should put effort into programs that bring students together and promote the creation of social capital.